Food Web Responses to Augmenting the Entomopathogenic Nematodes in Bare and Animal Manure-Mulched Soil - Duncan, L. W. (The Society of Nematologists, 2007)
Factorial treatments of entomopathogenic nematodes (EPN) and composted, manure mulches were evaluated for two years in a central Florida citrus orchard to study the post-application biology of EPN used to manage the root weevil, Diaprepes abbreviatus. Mulch treatments were applied once each year to study the effects of altering the community of EPN competitors (free-living bactivorous nematodes) and antagonists (nematophagous fungi (NF), predaceous nematodes and some microarthro-pods). EPN were augmented once with Steinernema riobrave in 2004 and twice in 2005. Adding EPN to soil affected the prevalence of organisms at several trophic levels, but the effects were often ephemeral and sometimes inconsistent. EPN augmentation always increased the mortality of sentinel weevil larvae, the prevalence of free-living nematodes in sentinel cadavers and the prevalence of trapping NF. Subsequent to the insecticidal effects of EPN augmentation in 2004, but not 2005, EPN became temporarily less prevalent, and fewer sentinel weevil larvae died in EPN-augmented compared to non-augmented plots. Manure mulch had variable effects on endoparasitic NF, but consistently decreased the prevalence of trapping NF and increased the prevalence of EPN and the sentinel mortality. Both temporal and spatial abundance of NF were inversely related to the prevalence of Steinernema diaprepesi, whereas Heterorhabditis zealandica prevalence was positively correlated with NF over time. The number of weevil larvae killed by EPN was likely greatest in 2005, due in part to non-target effects of augmentation on the endemic EPN community in 2004 that occurred during a period of peak weevil recruitment into the soil.